Analysis of Cybercrime Potential in E-Commerce Buying and Selling Transactions - Elisanti, Evi; Khaerudin, Ariy; Junaidi, Amir; Ardhani Putri, Hanuring Ayu; Muhtarom, Muhammad (Fakultas Syariah INSURI Ponorogo, 2024)
The research aims to analyze the potential for cybercrime in e-commerce buying and selling transactions. The research method used is normative juridical. The type of primary data is interviews and discussions related to e-commerce, and secondary data is library literature. Data collection techniques used literature studies, interviews, observation, and documentation. The data analysis technique is descriptive qualitative which is used in the form of an interactive analysis model. The research results show that the potential for cybercrime in e-commerce buying and selling transactions has increased significantly, including minimal knowledge, waste of money, being tempted by fake gifts, high levels of unemployment and poverty, and less strict government security policies. Forms of cybercrime in e-commerce include hacking, identity theft, data breach, phishing, spamming, pharming, pretexting, qui pro quo, and contacting the victim directly. Specific solutions are needed to overcome the cybercrime problem of e-commerce buying and selling, namely Backup, Use of SSL Certificates, Firewall, E-Commerce Security Plugin, Multilayer security, User and Staff Education. The conclusion of this research is that the potential for cybercrime in e-commerce buying and selling transactions has increased significantly so it is very necessary to prevent specific solutions in resolving cybercrime problems in e-commerce buying and selling transactions.